A atual legislação educacional brasileira para formação de professores: origens, influências e implicações nos cursos de licenciatura em matemática - Silva, Marcio Antonio da (2004)
The present work has the objective of researching the graduation of Mathematics teachers in Brazil, analyzing the proposals presented and the interpretations that are being done by coordinators of licensing courses in Mathematics concerning the updated official legislation to the teacher education in the present moment. In order to accomplish that, we have analyzed the historical origins, the theoretical influences mainly the reflective practice, according to Donald Schön, and the competences, according to Philippe Perrenoud the relations between theory and practice and the interferences of international fomentation agencies, such as World Bank, in the elaboration of official directives. Soon afterwards, we have done four interviews where coordinators of higher education institutions were invited to expose their ideas, doubts and suggestions concerning the reformulation of licensing courses in Mathematics due to the new demands imposed by the Resolutions 01 and 02 of CP/CNE in 2002. We have checked, according to the coordinators of licensing courses of Mathematics, that the fundamental concepts transmitted by the present legislation and the discussions are innocuous if compared to the serious problems the licensing courses in Mathematics are facing nowadays. By the way, this seems to be one of the great implications of the governmental proposes: being far from the reality of the courses. We have also checked that the governmental proposes were not totally put into practice in the courses, what should have happened in February 2004. On the other hand, the coordinators have proposed alternatives to overcome the existing contradictions in the elaboration of the official directives, what make us think that, with a little bit of information and the spread of the existing researches, other institutions of higher education will have remarkable results in the reformulation of their courses